Protocol for the COG-UK hospital-onset COVID-19 infection (HOCI) multicentre interventional clinical study: evaluating the efficacy of rapid genome sequencing of SARS-CoV-2 in limiting the spread of COVID-19 in UK NHS hospitals. Issue 4 (19th April 2022) - Blackstone, James; Stirrup, Oliver; Mapp, Fiona; Panca, Monica; Copas, Andrew; Flowers, Paul; Hockey, Leanne; Price, James; Partridge, David; Peters, Christine; de Silva, Thushan; Nebbia, Gaia; et al.
Abstract : Objectives: Nosocomial transmission of SARS-CoV-2 has been a significant cause of mortality in National Health Service (NHS) hospitals during the COVID-19 pandemic. The COG-UK Consortium Hospital-Onset COVID-19 Infections (COG-UK HOCI) study aims to evaluate whether the use of rapid whole-genome sequencing of SARS-CoV-2, supported by a novel probabilistic reporting methodology, can inform infection prevention and control (IPC) practice within NHS hospital settings. Design: Multicentre, prospective, interventional, superiority study. Setting: 14 participating NHS hospitals over winter–spring 2020/2021 in the UK. Participants: Eligible patients must be admitted to hospital with first-confirmed SARS-CoV-2 PCR-positive test result >48 hour from time of admission, where COVID-19 diagnosis not suspected on admission. The projected sample size is 2380 patients. Intervention: The intervention is the return of a sequence report, within 48 hours in one phase (rapid local lab processing) and within 5–10 days in a second phase (mimicking central lab), comparing the viral genome from an eligible study participant with others within and outside the hospital site. Primary and secondary outcome measures: The primary outcomes are incidence of Public Health England (PHE)/IPC-defined SARS-CoV-2 hospital-acquired infection during the baseline and two interventional phases, and proportion of hospital-onset cases with genomic evidence of transmission linkage following implementation of the intervention where such linkage was not suspected by initial IPC investigation. Secondary outcomes include incidence of hospital outbreaks, with and without sequencing data; actual and desirable changes to IPC actions; periods of healthcare worker (HCW) absence. Health economic analysis will be conducted to determine cost benefit of the intervention. A process evaluation using qualitative interviews with HCWs will be conducted alongside the study. Trial registration number: ISRCTN50212645 . Pre-results stage. This manuscript is based on protocol V.6.0. 2 September 2021.